2021
DOI: 10.3390/biom11111635
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic, Genetic, and Mechanistic Overlaps between Autism and Alzheimer’s Disease

Abstract: Autism spectrum disorder (ASD) and Alzheimer’s disease (AD) are neurodevelopmental and neurodegenerative disorders affecting two opposite ends of life span, i.e., childhood and old age. Both disorders pose a cumulative threat to human health, with the rate of incidences increasing considerably worldwide. In the context of recent developments, we aimed to review correlated symptoms and genetics, and overlapping aspects in the mechanisms of the pathogenesis of ASD and AD. Dementia, insomnia, and weak neuromuscul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 234 publications
(214 reference statements)
0
12
0
Order By: Relevance
“…In another study, PTPRD was identified as the significant gene associated with AD [ 29 ]. The MACROD2 , which was the neurodevelopmental-related gene, was reported as the risk loci of autism spectrum disorder [ 30 ], while the autism spectrum disorder had overlapping mechanisms of pathogenesis with AD [ 31 ]. Therefore, we suggested that the MACROD2 was associated with AD by affecting the autism spectrum disorder.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, PTPRD was identified as the significant gene associated with AD [ 29 ]. The MACROD2 , which was the neurodevelopmental-related gene, was reported as the risk loci of autism spectrum disorder [ 30 ], while the autism spectrum disorder had overlapping mechanisms of pathogenesis with AD [ 31 ]. Therefore, we suggested that the MACROD2 was associated with AD by affecting the autism spectrum disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence reports that neurodegenerative disease is more prevalent in adults with ASD (148). Alzheimer's disease (AD) is a neurodegenerative disease that has similar mechanisms supporting the pathogenesis of ASD (149). A key protein implicated in the pathology of AD is amyloid precursor protein (APP).…”
Section: Inflammatory and Immune Disease Associated With Autism Spect...mentioning
confidence: 99%
“…It is the most common cause of dementia, memory loss, depression and language impairments [ 136 ]. The main causes of AD include accumulation of amyloid β (Aβ) in the form of plaques [ 137 ], or deposition of Tau protein in the neurological tissues [ 138 ]. Declined levels of neurotransmitter acetylcholine (Ach) by the action of acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) also result in the onset of AD.…”
Section: Allicin As a Neuroprotective Agent To Fight Against Neurological Diseasesmentioning
confidence: 99%